Crossing the Boundaries: The Traditions of Kumaon and Nepal in Kumaoni Literature - Berry, Gayatri (Literary Studies, 2025)
Kumaon is a region located at the foothills of the Himalayas in Uttarakhand. It shares not only a boundary with Nepal but also a long cultural history that dates to the Doti kingdom. The paper proposes to look at the history of their shared traditions and the current changing environment of the region due to the immense rate of out-migration leading to the formation of several ‘ghost villages’ (i.e. villages with zero population) and its literary representation. The primary cause of migration is economic deprivation in the hills due to lack of employment. In tandem with the economic deprivation, the agrarian economy of the region is also faltering due to the climactic changes. Deeply embedded in Kumaoni and Nepali culture is the love and reverence towards nature. However, various factors like ill-planned construction of dams and racticeedion are disturbing the ecological and cultural balance. Agriculture depends upon rainfall that has become quite irregular due to the recent ecological imbalance, which is also driving wild animals out of their habitat and becoming a threat for human beings. Since Nepali-Kumaoni culture is centred on community, a community not just of humans but both human and non-human, the non-human does not stay untouched by the effect of migration and unplanned development. Thus, the cultural loss does not entail only the human’s way of living but also the loss of flora and fauna. Through Neil Evernden’s idea of “interrelatedness” and Christopher Manes’ idea of nature as a speaking subject, I argue that the ecocentric Nepali-Kumaoni culture is a part of the “self” of the Kumaonis and Nepalis which is suffering from dissociation.